Synthesis and Characterisation of Unsymmetrical Tetraarylstibonium Amides, Oximates and Carboxylates - SINGHAL, KIRAN; MISHRA, RAHUL; PRAKASH, OM (Asian Journal of Chemistry, 2010)
Several hitherto unreported pentacoordinated unsymmetrical amide, oximate and carboxylate complexes of the general formula R3R´SbL m-NO2C6H4] have been isolated and characterized by elemental analysis solid state infrared spectra, conductivity and molecular weight measurements. These complexes remain unaffected in the presence of water, methanol and carbon disulfide. However (Sb—O) and (Sb—N) bonds are cleaved in preference to (Sb—Ar) bond(s) by bromine and tellurium(IV) chloride. A few compounds were tested for and found to exhibit moderate to significant biological activity.